1999
DOI: 10.1016/s0014-5793(99)01718-4
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of a ligand‐induced conformational change in the catalytic core of Cdc25A

Abstract: The cell cycle control phosphatases Cdc25 are dual specificity phosphatases that dephosphorylate both phosphothreonine and phosphotyrosine residues on their substrate proteins. The determination of the apo-protein structure of Cdc25A revealed that this enzyme has a completely different fold compared to all other phosphatases crystallised to date. The conformation of the active site residues does not seem very suitable for catalysis in this unliganded structure. We have studied some structural features of the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…The results for ∆G are summarized in Table 1 where we used both the lowest energy frame and histogram peak shifting approaches (Section 2.3) to estimate ∆G for leucine dipeptide. The value of ∆S was found to be zero within uncertainty, consistent with the value found using eq (9). For each shifting approach, we tested four sets of shifting coordinates: backbone torsions only, all torsions, all torsions and bond angles, or all internal coordinates (torsions, angles and bond lengths).…”
Section: Leucine Dipeptidesupporting
confidence: 72%
See 1 more Smart Citation
“…The results for ∆G are summarized in Table 1 where we used both the lowest energy frame and histogram peak shifting approaches (Section 2.3) to estimate ∆G for leucine dipeptide. The value of ∆S was found to be zero within uncertainty, consistent with the value found using eq (9). For each shifting approach, we tested four sets of shifting coordinates: backbone torsions only, all torsions, all torsions and bond angles, or all internal coordinates (torsions, angles and bond lengths).…”
Section: Leucine Dipeptidesupporting
confidence: 72%
“…45 The superior convergence properties of the iterative method can be seen in Figure 2. The solid horizontal black line represents the independent, 4.0 µsec ∆G value obtained by using eq (9). The data are ∆G estimates using the singlestage shifting method, where backbone torsions were shifted according to the histogram peaks.…”
Section: Leucine Dipeptidementioning
confidence: 99%
“…Using the natural substrate the k cat/ K M pH rate profiles also showed a typical slope of −1 on the basic side, often assigned to general acid catalysis. It is also noteworthy that the necessary conformational change for catalysis in cdc25 was correctly predicted by MD simulations [25] as judged from a recent crystal structure [26].…”
Section: Structural Basis For Catalysismentioning
confidence: 74%
“…It is not quite clear which residue replaces the aspartic acid from the WPD loop and reacts as a general acid in the catalytic reaction of such PTPs. Some previous studies have shown that the general acid residue perhaps can be a part of the catalytic (H/V)C(X)5R(S/T) loop 49,50. The side chain conformation of such a residue would therefore define an active form for these phosphatases.…”
Section: Methodsmentioning
confidence: 99%